2011
DOI: 10.1017/s0963180111000296
|View full text |Cite
|
Sign up to set email alerts
|

The Concepts of Common Good and Public Interest: From Plato to Biobanking

Abstract: The expression “common good” usually conjures up benevolent associations: it is something to be desired, a worthy goal, and it would be a brave person who declared he or she was against the common good. Yet modern times have taught us to be critical and even suspicious of such grand rhetoric, leading us to query what lies behind this ambitious notion, who formulates what it stands for, and how such formulations have been reached.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…With its origins in Judaism and Hellenistic philosophy, the concept of the common good has been used in a diverse range of philosophical, political and economic traditions from Aristotle's philosophy to various subfields including health economics and political science (e.g. Diggs, 1973;Simm, 2011;Smith, 1999). Some ethics scholars have defined common good as "that order of society in which every member enjoys the possibility of realizing his true self by participating in the effects of the cooperation of all" (Messner, 1965, p. 124).…”
Section: Humanistic Provenance and 'Deep' Meaning Of The Common Goodmentioning
confidence: 99%
“…With its origins in Judaism and Hellenistic philosophy, the concept of the common good has been used in a diverse range of philosophical, political and economic traditions from Aristotle's philosophy to various subfields including health economics and political science (e.g. Diggs, 1973;Simm, 2011;Smith, 1999). Some ethics scholars have defined common good as "that order of society in which every member enjoys the possibility of realizing his true self by participating in the effects of the cooperation of all" (Messner, 1965, p. 124).…”
Section: Humanistic Provenance and 'Deep' Meaning Of The Common Goodmentioning
confidence: 99%
“…52 In addition, it is noted that wider ideas of the common good, public interest or the collective needs of society are not represented. 58,59 Some have suggested that autonomous authorisation represents a particular set of Western social and cultural values and is not simply transferable to other societies and cultural settings. 60 An alternative and more recent approach to informed consent, termed the 'fair transaction model', sets the idea of informed consent in the wider context of consent to other social transactions (e.g.…”
Section: Theories Of Informed Consent: Developing An Analytical Framementioning
confidence: 99%
“…Consequently, we suggest that, for health research, it is more appropriate to refer to stewardship rather than ownership of data. In addition, contributors to the research enterprise should carry a collective responsibility for information governance and the business objective must also meet a public interest test 17…”
Section: Resultsmentioning
confidence: 99%